AKTIVITAS ANTIMIKOSIS EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L.) - Didi Rohadi (Universitas Ahmad Dahlan, 2016)
Prevalence of Candidiasis is still in high level. Some antimycosis have been less effective so it needs to explore novel sources of antimycosis, one of candidate is the soursop leaves (Annona muricata L.) The aims of this study to observe antimycosis activity of the ethanol extract of soursop leaves at concentration of 15 %, 30 %, and 60 % against Candida albicans ATCC 10231 with agar diffusion method . The results showed that all of the ethanol extract of soursop leaves have exhibited antimycosis activity which concentration-dependent.